OPTIMASI KUALITAS PERUSAHAAN PRODUKSI BATU BATA DENGAN SISTEM PENDUKUNG KEPUTUSAN METODE AHP - Muh. Nurtanzis Sutoyo; Johar Nur Iin (Jurnal Sistem Informasi dan Informatika (Simika), 2024)
In the brick-making industry, the quality of the final product heavily relies on various factors, including the quality of raw materials, production techniques, environmental practices, and the effectiveness of quality management. This study employs the Analytical Hierarchy Process (AHP) method to evaluate and compare the performance of seven companies operating in the brick-making industry. The primary goal is to identify the company with the best product while considering sustainable practices and production efficiency. Through meticulous data collection and comprehensive analysis using AHP, this research successfully determined that Perus-G leads the industry with the highest score, which is 3.570. This result indicates that Perus-G consistently implements innovative production processes, prioritizes the use of high-quality raw materials, employs efficient production techniques, and adopts sustainable environmental practices. This research demonstrates that the Analytical Hierarchy Process (AHP) is effective as an analytical tool for optimizing the selection of brick-making companies. It enables stakeholders to make decisions based on both quantitative and qualitative assessments.